Weed Management in Plum - Peter J. Dittmar; Jeffrey G. Williamson (EDIS, 2012)
This revised 6-page fact sheet was written by Peter J. Dittmar and Jeffrey G. Williamson, and published by the UF Department of Horticultural Sciences, February 2012.